STUDI ETNOMATEMATIKA GARIS DAN SUDUT PADA MOTIF SENI RUMAH BUDAYA SUMBA - Dhajo, Maria Liberti; Sulistyorini, Yunis (Universitas Insan Budi Utomo, 2023)
Ethnomatematics is a bridge between culture and mathematics as well as mathematics and culture. This study aims to describe the results of an ethnomathematics study on the art motifs of the Sumba cultural house related to the mathematical concepts of lines and angles. The method used in this study is descriptive qualitative with an ethnographic approach. In this study, the ethnographic approach aims to describe and analyze culture based on mathematical concepts on lines and angles in the Sumba cultural house motif. Research data collection techniques were observation, interviews and documentation. The data collection instruments used were observation guidelines, interview guidelines and documentation. The instrument guide contains three aspects, namely historical aspects, philosophical aspects and mathematical aspects. The data analysis technique used in this study were data reduction, data presentation and conclusion. The technique used to test the validity of the data was the triangulation technique. The triangulation used is technical triangulation. The results showed that in Sumba culture houses there are various kinds of motifs such as turtle, crocodile, horse, chicken, deer, enga or plate motifs, mamuli, maraga, tala or gong, bhedu or tambor, pig's jaw, buffalo horn and anatou. The mathematical concept of lines and angles in the Sumba cultural house has various forms of lines and angles. The motifs are in the form of lines such as parallel lines, coincident lines and intersecting lines. Meanwhile, motifs that are in the form of angles such as acute angles, right angles, obtuse angles, straight angles and reflex angles.